Laundry gel bead content containing microcapsule essence as well as preparation method and application of laundry gel bead content
By optimizing raw materials and processes, selecting specific surfactants and solvents, and using a two-step feeding process, the laundry beads successfully contains higher content of microcapsule essence and hydrogenated castor oil, solving the problem of difficult suspension ability and stability. Problem, better suspension stability performance is achieved.
Patent Information
- Application Number
- CN202411561669.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
AI Technical Summary
When adding high-content microcapsule essence to existing laundry bead products, the suspension ability and stability are difficult to guarantee, and commercially available microcapsule essence contains high moisture, which increases the difficulty of formula development.
By optimizing raw materials and processes, selecting specific polyether anionic surfactants and solvents, adopting a two-step feeding process, first emulsifying the castor oil with propylene glycol to form a premix 1, and then adding other surfactants and microcapsule essence. The premix 2 is formed, and the cooling is reduced to promote the crystallization of hydrogenated castor oil, forming a suspension agent with a network structure.
Products containing higher content of microcapsule essence and hydrogenated castor oil in the laundry beads are realized, and the suspension stability is better, solving the problems of difficulty in dispersing microcapsule essence and incompatibility of suspension agents in the prior art.
Smart Images

Figure BDA0005118050310000071 
Figure BDA0005118050310000081 
Figure BDA0005118050310000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of daily chemicals, and in particular to a laundry bead content containing microcapsule essence, and a preparation method and application thereof. Background Art
[0002] In the field of detergents, long-lasting fragrance has always been one of the key functions that consumers pay the most attention to. In the prior art, in order to improve the fragrance effect, adding microcapsule fragrances has become the most common technical means in this field. However, since microcapsule fragrances can only be dispersed in the water phase, and during the application process, microcapsules have problems such as easy aggregation, easy sedimentation, and easy stratification. For this reason, various suspending agents need to be used simultaneously in current related products. Hydrogenated castor oil suspending agents are a type of suspending agent that is widely used.
[0003] Laundry detergent beads are a new type of detergent product that is currently popular. They are made of highly concentrated detergent wrapped in a water-soluble film. The structural characteristics of the water-soluble film of the beads prevent the liquid in the beads from containing too much water. The moisture content of commercially available laundry detergent beads is generally below 15%. Therefore, in order to achieve a better long-lasting fragrance effect in the detergent beads, the amount of microcapsule fragrance added to the product usually needs to be doubled, which brings more challenges to the product in terms of suspension ability and stability. In addition, the low water content of the laundry detergent beads and the large amount of added co-solvents also lead to the phenomenon of system incompatibility and easy stratification when conventional suspending agent products are applied to detergent beads.
[0004] Considering that laundry beads can be easily made into multi-cavity structures, different cavities of the beads can have different washing and care functions. Therefore, if a high content of microcapsule fragrance can be concentrated in one of the cavity structures, and only one cavity is used as the fragrance function cavity of the product, then, relative to the entire product, it is not necessary to add suspending agents to other cavities of the beads, thus saving a lot of costs and being more economical. But obviously, a higher content of microcapsule fragrance also places higher demands on the suspension capacity of the contents of the beads. In addition, the microcapsule fragrances currently available on the market usually contain 60-70% water, so when the amount of microcapsule fragrance used increases, there will be less water left for other components in the formula, which directly increases the difficulty of developing similar formulas.
[0005] In summary, how to apply high-content microencapsulated fragrances to laundry detergent beads and ensure their stability is technically very challenging and has always been a focus of attention in the industry. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a laundry condensate bead content containing microcapsule essence and a preparation method and application thereof. The present invention can successfully prepare a laundry condensate bead content with a higher content of microcapsule essence and HCO and better suspension stability through raw material optimization and process optimization.
[0007] The specific technical scheme of the present invention is: In the first aspect, the present invention provides a laundry detergent bead containing microcapsule fragrance, comprising the following components in mass percentage: hydrogenated castor oil (HCO) 0.1-2.0%, polyether anionic surfactant 7-14%, other surfactants 10-40%, propylene glycol 15-40%, other water-miscible solvents 10-35%, microcapsule fragrance 0.1-10%, other additives 0-5%, and water.
[0008] In the prior art, the method of applying a suspending agent to the contents of laundry beads is generally to first prepare a suspending agent with good performance using hydrogenated castor oil and other raw materials (such as surfactants and solvents), and then add the suspending agent together with functional components such as microcapsule fragrance to the laundry beads to prepare fragrance beads. However, the laundry beads prepared in this way can only contain a limited amount of microcapsule fragrance while ensuring stability (microcapsule fragrance is difficult to disperse in a high-viscosity system), so it is impossible to prepare laundry beads with a long-lasting fragrance.
[0009] To this end, the present invention first solves the above technical difficulties from the perspective of emulsifier and solvent types, as follows: (1) Selection of emulsifier: The present invention finds that the polyether anionic surfactant of a specific structure has a better emulsifying effect on hydrogenated castor oil, and the obtained emulsion has better high temperature stability, so that under certain process conditions, it can ensure that the system is stably maintained in a low viscosity state before adding the microcapsule flavor, thereby ensuring that the microcapsule flavor is fully dispersed (if ordinary surfactants such as sulfonic acid and AEO are used as emulsifiers, although HCO can also be emulsified, the paste temperature of the relevant system emulsion is relatively high (about 70-80°C), at this temperature the system viscosity is too high or even paste-like, so it is difficult to disperse the microcapsule flavor); after adding the microcapsule flavor, the temperature is lowered and crystallized to form a suspending agent with a network structure, so that the microcapsule flavor is stably suspended in the network structure. Studies have shown that anionic surfactants have a relatively stronger emulsifying ability for vegetable oils and fats, while non-ionic surfactants have a larger solubilization space and a relatively stronger solubilization ability because the EO head group accounts for a larger proportion in their molecules and there is a fence layer in the self-assembly structure. Compared with conventional anionic surfactants such as LAS, SDS, fatty acid soaps, etc., the polyether anionic surfactants used in the present invention have a portion of polyether components blocked in the molecular structure, which allows it to retain the overall anionic advantages while also having some non-ionic capabilities, which is beneficial to improving the emulsion stability in the emulsification process of the present invention to a certain extent.
[0010] (2) Selection of solvent: The solvents in the present invention are divided into two categories. One category is propylene glycol. Propylene glycol has a relatively high polarity and can dissolve polyether anionic surfactants such as AES in the presence of a very small amount of water. Meanwhile, HCO has a relatively low polarity and has a very low solubility in propylene glycol in the temperature range of 70 to 95° C. in the present invention. The other category is other solvents that are miscible with water and can dissolve components such as polyether nonionic surfactants with relatively low polarity. Thus, the overall premix 2 formed has a different polarity from the premix 1, generally showing a lower polarity and a strong solubility in HCO.
[0011] The preparation process of the laundry beads of the present invention can be roughly summarized as follows: First, HCO is emulsified with a propylene glycol and anionic surfactant solvent system to prepare an emulsion whose internal phase is HCO. Since propylene glycol has poor solubility in HCO, the molten HCO and the emulsifier are more inclined to be in the internal phase of the emulsion, thereby obtaining a premix 1. Secondly, a premix 2 consisting of other surfactants (such as nonionic surfactants such as AEO) with relatively better solubility in HCO, other solvents miscible with water that have a polarity difference with propylene glycol, and microcapsule fragrances is added to the premix 1, and the temperature is lowered to promote the crystallization of HCO, thereby forming a structurant. In this process, the difference in polarity of different solvents and the difference in solubility of HCO in different systems accelerate the crystallization of HCO from the original internal phase of the emulsion, and further induce the crystallization of HCO in a high-content solvent system.
[0012] In summary, the present invention provides a possibility for preparing laundry beads containing high-concentration microcapsule fragrance by selecting specific surfactants and solvents.
[0013] Preferably, the contents of the laundry beads include the following components in percentage by mass: 0.5-1.5% hydrogenated castor oil, 7-14% polyether anionic surfactants, 20-40% other low-water content surfactants, 20-40% propylene glycol, 10-30% other water-miscible solvents, 0.1-5% microcapsule flavors, 0-5% other additives, and water.
[0014] Preferably, the other solvents miscible with water include, but are not limited to, one or more of glycerol, ethylene glycol, polyethylene glycol and glycerol acetone.
[0015] Preferably, the polyether anionic surfactant is a carboxylate or sulfate surfactant of EO and / or PO and / or BO; further preferably, the polyether anionic surfactant includes but is not limited to one or more of fatty alcohol polyether sulfate (AES), fatty alcohol polyether carboxylate (AEC), modified oil ethoxylate sodium sulfonate (SNS-80), and alcohol ether sulfate Extended surfactant, and the most preferred is fatty alcohol polyether sulfate (AES).
[0016] Compared with conventional anionic surfactants such as LAS, SDS, fatty acid soaps, etc., the polyether anionic surfactants used in the present invention have a portion of polyether components blocked in the molecular structure, which allows it to retain the overall anionic advantages while also having some non-ionic capabilities, which is beneficial to improving the emulsion stability in the emulsification process of the present invention to a certain extent.
[0017] Preferably, the other surfactant is a polyether nonionic surfactant; further preferably, the polyether nonionic surfactant includes but is not limited to one or more of fatty alcohol alkoxylates, fatty acid ester ethoxylates, oil ethoxylates and fatty alcohol amide ethoxylates.
[0018] In a second aspect, the present invention provides a method for preparing the above laundry beads, comprising the following steps: 1) Dissolve a polyether anionic surfactant in propylene glycol, add hydrogenated castor oil and emulsify it to uniformly disperse it in the system to obtain a premix 1.
[0019] 2) Heat premix 1 to above the melting point of hydrogenated castor oil (about 85° C.), add hydrogenated castor oil, melt and homogenize, and fully emulsify and disperse the hydrogenated castor oil in premix 1.
[0020] 3) Add other surfactants and microcapsule flavors to other solvents miscible with water to obtain premix 2.
[0021] 4) Cooling premix 1 under homogenization conditions until the temperature drops to 50-65° C., stopping cooling and homogenizing, adding premix 2 under stirring, rapidly cooling to 30-50° C., and keeping the temperature to induce and promote crystallization of hydrogenated castor oil.
[0022] 5) After the heat preservation is completed, other additives are added and the material is discharged to obtain the laundry beads containing microcapsule fragrance.
[0023] Note: The water in the formula is the water contained in other raw materials, so there is generally no separate adding step.
[0024] In order to prepare the laundry beads with high concentration of microcapsule fragrance, in addition to the optimization from the perspective of raw materials, the present invention further optimizes the preparation process.
[0025] The present invention adopts a unique two-step feeding process, and its steps and principles are as follows: In the first step, HCO is dispersed and emulsified using propylene glycol as a solvent to prepare a relatively high concentration HCO emulsion. Since propylene glycol has poor solubility in HCO, the molten HCO and the emulsifier are more inclined to be in the inner phase of the emulsion, thereby obtaining a premix 1.
[0026] In the second step, the premix 2 composed of other surfactants (such as nonionic surfactants such as AEO) with relatively better solubility for HCO, other solvents miscible with water and having poor polarity with propylene glycol, and microcapsule flavors is added to the premix 1. Since the temperature of premix 2 is relatively lower, it can cool the system, induce HCO crystallization, and then form a structurant. The possible mechanism is: on the one hand, the two-step feeding process can achieve faster cooling of the system, promote HCO crystallization, shorten the process time, and is relatively more energy-efficient; on the other hand, after the addition of premix 2, the difference in polarity of different solvents and the difference in solubility of HCO in different systems accelerate the crystallization of HCO from the original emulsion phase, and further induce HCO to crystallize in the high-content solvent system; on the other hand, the microcapsule flavor in premix 2 is added before the network structure suspension is generated, that is, the microsphere structure of the microcapsule flavor participates in the formation of the final suspension structure, so it is more compatible with the system and has better compatibility stability.
[0027] In summary, the present invention is different from the conventional method. It first disperses and emulsifies HCO with a specific part of the solvent and a specific part of the surfactant in the bead formula, and then adds another part of the solvent and another part of the specific surfactant in the bead formula to induce HCO to form a structure. The combination of the two phases is equivalent to indirectly realizing in-situ structure generation in the bead content. Compared with the traditional method of introducing external structure, the present invention can add a higher content of microcapsule essence and a higher content of HCO, so the suspension stability performance is better.
[0028] Preferably, in step 1), the concentration of the polyether anionic surfactant in the premix 1 is 20 to 50 wt%.
[0029] The present invention finds that the concentration of the polyether anionic surfactant in the premix 1 in step 1) has a certain influence on the suspension ability of the final product, which is generally manifested as the higher the surfactant concentration, the more stable the emulsion formed, which is reflected in the tendency of the yield stress of the sample to increase. However, when the concentration of the surfactant is too high, it is easy to cause a significant increase in the viscosity of the system, thereby affecting the homogenization efficiency. On the contrary, if the surfactant concentration is low, the yield stress of the prepared suspension is small.
[0030] Preferably, in step 1) and step 2), the pH of premix 1 and premix 2 are respectively adjusted to 6-8.
[0031] Preferably, in step 4), the rate of the first cooling is 0.5-3.0°C / min.
[0032] If the temperature drops too quickly, HCO may crystallize too quickly, causing it to break the emulsion prematurely and form a structuring agent (suspending agent).
[0033] Preferably, in step 4), the temperature of the added premix 2 is 20-40°C.
[0034] Preferably, in step 4), the insulation time is 0.5 to 3.5 h.
[0035] In a third aspect, the present invention provides a use of the above-mentioned laundry condensate bead contents in the preparation of fragrance condensate beads with a long-lasting fragrance retention function: the laundry condensate bead contents are wrapped in a condensate bead water-soluble film to prepare fragrance condensate beads.
[0036] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention uses a polyether anionic surfactant with a specific structure to emulsify hydrogenated castor oil. The resulting emulsion has better high temperature stability, which can ensure that the system can stably maintain a low viscosity state before adding the microcapsule flavor, thereby ensuring that the microcapsule flavor is fully dispersed; after adding the microcapsule flavor, the system is cooled and crystallized to form a suspending agent with a network structure, so that the microcapsule flavor is stably suspended in the network structure.
[0037] (2) The solvents in the present invention are divided into two categories. In the preparation process of the contents of the laundry beads of the present invention: first, HCO is emulsified with propylene glycol to prepare an HCO emulsion. Since propylene glycol has poor solubility in HCO, the molten HCO and the emulsifier are more inclined to be in the inner phase of the emulsion, thereby obtaining premix 1. Secondly, other surfactants with relatively better solubility in HCO and other water-miscible solvents with poor polarity in premix 1 and microcapsule fragrances are made into premix 2 and added to premix 1, and the temperature is lowered to promote the crystallization of HCO, thereby forming a structurant. In this process, the difference in polarity of different solvents and the difference in solubility of HCO in different systems accelerate the crystallization of HCO from the original inner phase of the emulsion, and further induce the crystallization of HCO in the high-content solvent system.
[0038] (3) The present invention adopts a unique two-step feeding process to prepare the laundry beads contents. The present invention first disperses and emulsifies HCO with a specific part of the solvent and a specific part of the surfactant in the bead formula, and then adds another part of the solvent and another part of the specific surfactant in the bead formula to induce HCO to form a structure. The combination of the two phases is equivalent to indirectly realizing in-situ structure generation in the bead contents. Compared with the traditional method of introducing external structure, the present invention can successfully produce laundry beads contents with higher content of microcapsule fragrance and HCO and better suspension stability. DETAILED DESCRIPTION
[0039] The following cases further describe the present invention, but the protection scope of the present invention is not limited thereto.
[0040] The professional terms and technical means used in the present invention have the same meanings as those generally understood by those skilled in the art. Unless otherwise specified, the various reagents, raw materials, equipment, etc. in the present invention are commonly used reagents, raw materials, equipment understood by those skilled in the art and are all commercially available.
[0041] The present invention is further described below with reference to the Examples. Unless otherwise specified, percentages are by weight (wt%) and temperatures are in °C. "Alkyl" is a substituted or unsubstituted saturated hydrocarbon radical having from one to twenty-two carbon atoms in a straight or branched arrangement. Unless otherwise specified, an alkyl group is unsubstituted.
[0042] Overall embodiment In the first aspect, a laundry detergent bead containing microcapsule fragrance includes the following components in percentage by mass: 0.1-2.0% hydrogenated castor oil (HCO), 7-14% polyether anionic surfactant, 10-40% other surfactants, 15-40% propylene glycol, 10-35% other water-miscible solvents, 0.1-10% microcapsule fragrance, 0-5% other additives, and water.
[0043] In some preferred implementation cases, the contents of the laundry beads include the following components in mass percentage: 0.5-1.5% hydrogenated castor oil, 7-14% polyether anionic surfactants, 20-40% other low-water content surfactants, 20-40% propylene glycol, 10-30% other water-miscible solvents, 0.1-5% microcapsule flavors, 0-5% other additives, and water.
[0044] In some preferred implementation cases, the other solvents miscible with water include, but are not limited to, one or more of glycerol, ethylene glycol, polyethylene glycol and glycerol acetone, and glycerol is further preferred.
[0045] In some preferred implementation cases, the polyether anionic surfactant is a carboxylate or sulfate surfactant containing EO and / or PO and / or BO; further preferably, the polyether anionic surfactant includes but is not limited to one or more of fatty alcohol polyether sulfate (AES), fatty alcohol polyether carboxylate (AEC), modified oil ethoxylate sodium sulfonate (SNS-80), and alcohol ether sulfate Extended surfactant, and the most preferred is fatty alcohol polyether sulfate (AES).
[0046] In some preferred implementation cases, the other surfactant is a polyether nonionic surfactant; further preferably, the polyether nonionic surfactant includes but is not limited to one or more of fatty alcohol alkoxylates, fatty acid ester ethoxylates, oil ethoxylates and fatty alcohol amide ethoxylates.
[0047] In a second aspect, a method for preparing the contents of the laundry beads comprises the following steps: 1) Dissolve a polyether anionic surfactant in propylene glycol, add hydrogenated castor oil and emulsify it to uniformly disperse it in the system to obtain a premix 1.
[0048] In some preferred implementation cases, in step 1), the concentration of the polyether anionic surfactant in the premix 1 is 20-50 wt%.
[0049] In some preferred implementation cases, step 1) adjusts the pH of the premix 1 to 6-8.
[0050] 2) Heat premix 1 to above the melting point of hydrogenated castor oil (about 85° C.), add hydrogenated castor oil, melt and homogenize, and fully emulsify and disperse the hydrogenated castor oil in premix 1.
[0051] In some preferred implementation cases, in step 2), the pH of the premix 2 is adjusted to 6-8.
[0052] 3) Add other surfactants and microcapsule flavors to other solvents miscible with water to obtain premix 2.
[0053] 4) Cooling premix 1 under homogenization conditions until the temperature drops to 50-65° C., stopping cooling and homogenizing, adding premix 2 under stirring, rapidly cooling to 30-50° C., and keeping the temperature to induce and promote crystallization of hydrogenated castor oil.
[0054] Note: The water in the formula is the water contained in other raw materials, so there is no separate adding step.
[0055] In some preferred implementation cases, in step 4), the rate of the first cooling is 0.5-3.0°C / min.
[0056] In some preferred implementation cases, in step 4), the temperature of the added premix 2 is 20-40°C.
[0057] In some preferred implementation cases, in step 4), the insulation time is 0.5 to 3.5 hours.
[0058] 5) After the heat preservation is completed, other additives are added and the material is discharged to obtain the laundry beads containing microcapsule fragrance.
[0059] In a third aspect, a fragrance gel bead with a long-lasting fragrance retention function is prepared by wrapping the contents of the laundry gel bead in a gel bead water-soluble film to prepare the fragrance gel bead.
[0060] Specific Examples and Comparative Examples.
[0061] The raw materials used in the present invention are all commercially available industrial raw materials, and different surfactants have different water contents.
[0062] For example, LAS is solid sodium alkylbenzene sulfonate; sodium fatty alcohol polyether sulfate (AES), the content is 70wt%, and the rest is water; sodium oil ethoxylate sulfonate (SNS-80), light chemical industry, the content is 70wt%, and the rest is water; sodium alcohol ether sulfate Extended surfactant, Lianhong, the content is 70wt%, and the rest is water; AEO-9, the content is 99wt%; SOE-N-60, light chemical industry, the content is 99wt%; FMEE, light chemical industry, the content is 99wt%; glycerol, the content is 95wt%, and the rest is water; microcapsule flavor (FRESH CAPS173), Givaudan, the core material is floral and fruity flavor, the capsule material is polyurea, the solid content is 30wt%, and the rest is water.
[0063] Unless otherwise specified, the contents in the table below are pure addition amounts. If the raw materials already contain a certain amount of water, water will inevitably be introduced into the formula, which is marked as introduced water below.
[0064] Example 1 and Comparative Examples 1-4 Table 1: Sample formulations and sample properties of Comparative Examples 1-4 and Example 1 The specific preparation methods of the samples of Comparative Examples 1-4 and Example 1 are as follows: (1) Dissolve 12 parts of LAS or AEO-9 or AES in 37 parts of propylene glycol, adjust the pH to about 8, heat to 92°C, add 1.5 parts of HCO, wait for the HCO to melt, and start homogenization. This is premix 1; (2) cooling the premix 1 at a cooling rate of 1.5° C. / min under homogenization conditions, and observing the change in the liquid state of the premix 1 during the cooling process; when the temperature drops to about 60° C., the homogenization and cooling are stopped; (3) Premix 20 parts of AEO-9, 10 parts of microcapsule essence and 20 parts of glycerin or propylene glycol according to the proportion in Table 1, and adjust the pH to about 8, which is premix 2. Add 30°C premix 2 to premix 1 at about 60°C, and lower the overall temperature to about 48°C. Maintain mechanical stirring and keep warm for 1.0h to obtain the fragrance bead liquid.
[0065] The sample tests are as follows: Yield stress test: tested with Brookfield RST rheometer, temperature 25°C, shear rate scanning range 0.01~100s -1 , 0.1~100s -1 The data were fitted with the Herschel-Bulkley model, and the stability index R 2 Must be greater than 0.999.
[0066] Stability test: Place relevant samples under corresponding conditions and observe whether the samples have unstable phenomena such as stratification. Comparative Examples 1 and 2 and Example 1 in Table 1 use three representative surfactants in the field as emulsifiers for emulsifying HCO in propylene glycol solvent. The results show that when LAS and AEO-9 are used as emulsifiers, premix 1 becomes a viscous liquid and a paste-like solid respectively during the cooling process, while when AES is used as an emulsifier, premix 1 is still a low-viscosity emulsion. This shows that the emulsified structure formed by AES and HCO is relatively stable during the cooling process.
[0067] Comparing Example 1 with Comparative Examples 3 and 4 in Table 1, it can be seen that different solvents in premixes 1 and 2 will affect the stability of the sample. For example, in Comparative Example 3, premix 1 and premix 2 use the same propylene glycol, and in Comparative Example 4, premix 1 and premix 2 use the same glycerol as solvent. The yield stress of the samples prepared by both is lower than that of Example 1, indicating that the differentiated solvent system in the two-step process is conducive to structure formation. At the same time, when Comparative Example 4 uses glycerol with a higher polarity as the solvent, the moisture content of the prepared sample is higher, so there is a phenomenon of soft beads after the initial wrapping into beads.
[0068] Examples 2-5 and Comparative Example 5 Table 2: Sample formulations and sample properties of Examples 2-5 and Comparative Example 5 The preparation methods of the samples of Examples 2-5 and Comparative Example 5 are roughly the same as those in Table 1 above.
[0069] The amount of emulsifier AES in Table 2 was fixed, and the solvent content in premix 1 was gradually increased to prepare the sample. The test results show that during the emulsification process in premix 1, a higher emulsifier concentration may be beneficial to the final suspension ability of the sample. Obviously, the proportion of solvent in premix 1 and premix 2 is different under different emulsifier concentrations. At the same time, from the appearance of the beads, it seems that a high glycerol content will cause the beads to appear relatively soft. Therefore, it is generally preferred that the propylene glycol content is 20% to 40% and the glycerol content is 10% to 30%.
[0070] Examples 6-10 Table 3: Sample formulations and sample properties of Examples 6-10 The preparation methods of the samples of Examples 6-10 above are roughly the same as those in Table 1 above.
[0071] Table 3 expands the types of polyether anionic surfactants used in premix 1 and premix 2. The results show that the emulsifier in premix 1 can be extended to polyether anionic surfactants with similar structures, such as SNS-80, sodium alcohol ether sulfate extended surfactants and HCO, which can form emulsified compositions with good stability; the surfactant in premix 2 can also be extended to other polyether nonionic surfactants with low water content.
[0072] Further, the other solvents miscible with water in the premix 2 can also be extended to other solvents similar to glycerol, such as a mixture of one or more of ethylene glycol, polyethylene glycol, and acetone acetal (ACM). However, the other solvents used must be miscible with water, and when different solvents are used, the optimal ratio of the premix 1 and the premix 2 can be optimized and determined by a limited number of small tests, and the present invention will not repeat them one by one.
[0073] Example 10 was selected to conduct a sensory test on the fragrance retention intensity and fragrance retention effect of the laundry beads of the present invention. The results are shown in Table 4.
[0074] Table 4: Sensory evaluation of fragrance intensity of samples of Example 10 (score on a 7-point scale) Group Fragrance strength rating Score of fragrance intensity after 120 hours Example 10 6.5 6.4 Commercially available ordinary laundry gel beads 1 (without capsule fragrance) 2.5 2.0 Commercially available ordinary laundry beads 2 (a small amount of capsule fragrance) 4.3 4.0 Note: The towels were washed at a concentration of 0.5 g / L in a washing machine, and 15 random reviewers were asked to rate the intensity of the fragrance retained in the towels (evaluation after rubbing).
[0075] The results show that Example 10 prepared by the technology of the present invention is significantly superior to the commercially available gel beads product without capsule flavor or with less capsule flavor added in terms of fragrance retention intensity, and also has a long-lasting fragrance effect.
[0076] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0077] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A laundry gel bead containing microcapsule fragrance, characterized in that The following components are included in mass percentage: Hydrogenated castor oil 0.1~2.0%, Polyether anionic surfactant 7~14%, Other surfactants 10~40%, Propylene glycol 15~40%, Other solvents miscible with water 10~35%, Microcapsule flavor 0.1~10%, Other additives 0~5%, water.
2. The laundry condensate according to claim 1, characterized in that The following components are included in mass percentage: Hydrogenated castor oil 0.5~1.5%, Polyether anionic surfactant 7~14%, Other low water content surfactants 20~40%, Propylene glycol 20~40%, Other solvents miscible with water 10~30%, Microcapsule flavor 0.1~5%, Other additives 0~5%, water.
3. The laundry condensate according to claim 1 or 2, characterized in that: The other solvent miscible with water is selected from one or more of glycerol, ethylene glycol, polyethylene glycol and glycerol acetone acetal.
4. The laundry condensate according to claim 1 or 2, characterized in that: The polyether anionic surfactant is a carboxylate or sulfate surfactant containing EO and / or PO and / or BO; The other surfactant is a polyether type nonionic surfactant.
5. The laundry condensate according to claim 4, characterized in that: The polyether type anionic surfactant includes one or more of fatty alcohol polyether sodium sulfate, fatty alcohol polyether sodium carboxylate, modified oil ethoxylate sodium sulfonate, and alcohol ether sulfate ester salt Extended surfactant; The polyether type nonionic surfactant includes one or more of fatty alcohol alkoxylates, fatty acid ester ethoxylates, oil ethoxylates and fatty alcohol amide ethoxylates.
6. A method for preparing the contents of laundry beads according to any one of claims 1 to 5, characterized in that include: 1) dissolving a polyether anionic surfactant in propylene glycol, adding hydrogenated castor oil and emulsifying to obtain a premix 1; 2) Heat premix 1 to above the melting point of hydrogenated castor oil, add hydrogenated castor oil, and melt and homogenize; 3) adding other surfactants and microcapsule flavors to other solvents miscible with water to obtain premix 2; 4) Cool premix 1 to 50-65°C while homogenizing, stop cooling and homogenizing, add premix 2 while stirring, cool to 30-55°C, and keep warm to induce crystallization of hydrogenated castor oil; 5) Add other additives to obtain the contents of laundry beads.
7. The preparation method according to claim 6, characterized in that: In step 1), the concentration of the polyether anionic surfactant in the premix 1 is 20-50 wt%.
8. The preparation method according to claim 6, characterized in that: In step 1) and step 2), the pH of premix 1 and premix 2 are adjusted to 6-8 respectively.
9. The preparation method according to claim 6, characterized in that: In step 4), The first cooling rate is 0.5~3.0℃ / min; The temperature of the added premix 2 is 20-40°C; The insulation time is 0.5~3.5h.
10. Use of the laundry condensate content according to any one of claims 1 to 5 or the laundry condensate content obtained by the preparation method according to any one of claims 6 to 9 in preparing fragrance condensate beads, characterized in that: The contents of the laundry beads are wrapped in a water-soluble film to prepare fragrance beads.